2009
DOI: 10.1021/ct9003806
|View full text |Cite
|
Sign up to set email alerts
|

Using Correlated Monte Carlo Sampling for Efficiently Solving the Linearized Poisson−Boltzmann Equation Over a Broad Range of Salt Concentration

Abstract: Dielectric continuum or implicit solvent models provide a significant reduction in computational cost when accounting for the salt-mediated electrostatic interactions of biomolecules immersed in an ionic environment. These models, in which the solvent and ions are replaced by a dielectric continuum, seek to capture the average statistical effects of the ionic solvent, while the solute is treated at the atomic level of detail. For decades, the solution of the three-dimensional Poisson-Boltzmann equation (PBE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 96 publications
1
8
0
Order By: Relevance
“…Grids with common dimensions and alignments were generated for each separate binding partner and complex. The ACG predictions of ΔG el and ΔΔG el were corroborated by similar computations with APBS 19 and an in-house stochastic linear PB solver 5-7 (results not shown).…”
Section: Methodssupporting
confidence: 57%
“…Grids with common dimensions and alignments were generated for each separate binding partner and complex. The ACG predictions of ΔG el and ΔΔG el were corroborated by similar computations with APBS 19 and an in-house stochastic linear PB solver 5-7 (results not shown).…”
Section: Methodssupporting
confidence: 57%
“…The correlated finite difference (CFD) method introduces an artificial correlation between the KMC trajectories for the positively and negatively strained diffusion systems to reduce the statistical error. [29,30] The relative statistical error of CFD is…”
Section: B Correlated Finite Difference Methodsmentioning
confidence: 99%
“…A stochastic approach utilizing Monte Carlo methods for solving the PBE was developed by Mascagni, Fenley and co-workers and was shown that the stochastic based linear 3D PBE solvers have very low memory demands [64, 121, 125, 150] . It was demonstrated that by applying series of numerical optimizations one can make the computational time of these Monte Carlo LPBE solvers competitive with deterministic methods.…”
Section: Mathematical and Computational Developmentsmentioning
confidence: 99%